ANÁLISE PÓS-OCUPAÇÃO DE ÁREAS LIVRES DO CONJUNTO HABITACIONAL TANCREDO NEVES, TERESINA-PI - Costa, Isadora; Silveira, Ana Lucia (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The free areas in the housing complexes are important places for leisure, sports and living together. However, these areas often do not allow these activities for lack of maintenance and change of their main purpose. This work has as objective the post-occupation evaluation of the free areas of the Housing Tancredo Neves, located in Teresina-PI, with emphasis on the constructive changes made on the original project. The research also aimed to relate these changes to the way of life of the residents and their desires. The methodology adopted in the research was the indicative Post-Occupational for functional and behavioral variables. The techniques adopted were the application of questionnaires with the residents of the housing, interviews and "wishes poem", in addition to site visits for "walkthrough" analysis. The research showed that although the alterations were made in an irregular way, they were the result of the appropriation of the users' free spaces.